Curricular Innovation and Cultural Preservation: Implementing the Merdeka Curriculum in Balinese Language Teaching - Widana, I Nengah Adi; Jayawangsa, I Gusti Agung Rai; Tangkas, Made Reland Udayana; Putra, Made Susila; Dwijayanthi, Ni Made Ari; Jaya, Made Suardika; Suari, A. A. Pt. (Universitas Pendidikan Ganesha, 2025)
The implementation of the Merdeka Curriculum in Balinese language subjects still faces various conceptual and technical challenges that have not been fully resolved. This study aims to analyze in depth the implementation of the Merdeka Curriculum in Balinese language learning. This study uses a mixed methods approach with a quantitative and qualitative descriptive design. The research subjects consisted of Balinese language teachers at the junior high school and high school levels who were selected through purposive sampling. Data were collected through questionnaires, interviews, observations, and document analysis. Research instruments included teacher readiness questionnaires, interview guidelines, observation checklists, and data recording tools. Data were analyzed using descriptive statistics and thematic analysis. The results of the study indicate that the implementation of the Merdeka Curriculum in Balinese is classified as “fully implemented” with an implementation achievement ranging from 54.69% to 71.88%. The dimensions analyzed include policy understanding, learning objective formulation, lesson plan/teaching module development, learning implementation, and assessment. The main obstacles include internal constraints such as difficulties in formulating derivative learning objectives and changes in the learning paradigm, as well as external constraints such as limited learning resources and a lack of specific training. The solutions implemented include self-training, the formation of learning communities, and collaboration through MGMP. This study contributes to strengthening the implementation strategy of the Merdeka Curriculum, particularly in terms of culture-based local content.